Study on dysphagia from 2012 to 2021: A bibliometric analysis via CiteSpace - Sun, Weiming; Kang, Xizhen; Zhao, Na; Dong, Xiangli; Li, Shilin; Zhang, Gaoning; Liu, Guanxiu; Yang, Yang; Zheng, Chafeng; Yu, Guohua; Shuai, Lang; Feng, Zhen (Frontiers in Neurology, 2022)
Objectives This study aims to review the documents on dysphagia, summarize the research direction, analyze the research hot spots and frontiers, report the research trends, and provide new ideas for future development in the field via CiteSpace. Methods We retrieved articles on dysphagia published between 2012 and 2021 from the Web of Science Core Collection database. We downloaded the entire data and utilized CiteSpace version 5.8.R3 (64-bit) to analyze the number of publications annually, cited journals, countries, institutions, authors, cited authors, cited references, and keywords. We visualized the data with a knowledge map, collaborative network analysis, cluster analysis, and strongest citation burst analysis. Results We obtained 14,007 papers with a continually increasing trend over time. The most productive country and institute in this field were the United States (4,308) and Northwestern University (236), respectively. Dysphagia (5,062) and Laryngoscope (2,812) were the most productive journals, Elizabeth Ward had the highest number of publications (84), and Logeman et al.'s article (centrality: 0.02) was the most referenced. The most common keywords were dysphagia, management, quality of life, deglutition disorder, diagnosis, aspiration, prevalence, children, outcome, and oropharyngeal dysphagia. Conclusion This study analyzed the current literature on dysphagia via CiteSpace and identified its research hot spots and frontiers. The prevalent global trends in dysphagia research and the growing public awareness about healthcare and quality of life suggest that research on dysphagia will gain popularity with further breakthroughs.